The Effect of Profitability, Company Size, and Tunneling Incentive on Tax Avoidance with Transfer Pricing as a Moderating Variable - Roji Rohmani; Aminul Amin (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Tax avoidance is one of the ways carried out by taxpayers as an effort to reduce the burden of taxes paid legally by utilizing the gray area of taxes. However, in 2020 state losses reached Rp. 68.7 trillion due to tax avoidance. This study aims to examine the effect of profitability, company size, and tunneling incentives on tax avoidance with transfer pricing as a moderation. The research population is manufacturing companies listed on the IDX in 2019-2021. The research sample was 29 companies, selected using the purposive sampling method. This research is a quantitative study using Moderated Regression Analysis (MRA). The results of this study show that profitability, tunneling incentives and transfer pricing have a positive effect on tax avoidance.  The size of the company has no effect on tax avoidance.   Transfer pricing has been shown to moderate the effect of profitability and company size on tax avoidance, while in the tunneling incentive variable, transfer pricing has not been shown to moderate the effect of the tunnelling incentive variable on tax avoidance.